Implementation of Library Transformation Policy Based on Social Inclusion of the Central Sulawesi Provincial Library and Archives Office - Yunus, Yuniarti; Daswati, Daswati; Natsir, Nawawi (Faculty of Law, Universitas Pekalongan, 2024)
The This study examines the implementation of social inclusion-based library transformation policy in the Library and Archives Service of Central Sulawesi Province. Using a qualitative descriptive approach, this research analyzes the planning, implementation, monitoring, and evaluation processes of the policy. Factors influencing policy implementation are identified, including leadership commitment, budget support, and challenges related to human resources and infrastructure. The findings indicate that despite facing several obstacles, this policy has positively impacted increasing public access and participation in library activities. Recommendations include enhancing human resource capacity, strengthening stakeholder collaboration, and conducting regular evaluations to ensure policy effectiveness in realizing inclusive libraries in Central Sulawesi